Prevalence and risk-factors of early childhood caries among 2-6-year-old Anganwadi children in Nellore district, Andhra Pradesh, India: A cross-sectional survey - K Vandana; S Harikrishna Raju; Reddeppa Reddy Badepalli; J Narendrababu; Chandrasekhara Reddy; K M Sudhir (Wolters Kluwer Medknow Publications, 2018)
Purpose/Objectives: The objective of this study is to study the prevalence and associated risk determinants of early childhood caries (ECC) among preschool children. Materials and Methods: A cross-sectional descriptive study was designed to assess the ECC prevalence and associated risk factors among preschool children in Anganwadi of Nellore district using a standardized questionnaire. Results: A total of 550 study participants of age 2-6 years are enrolled in this cross-sectional study. Mean age of the participants was 4.39 ± 0.89 years. Most of the study participants (38%) were in the age of 5 years. When gender wise comparison was made girls represented 62% and boys 38% of the total population. When the risk factors were assessed for their association with caries experience, socioeconomic status, mother's schooling at child's birth, duration of using bottle, and bottle feeding while sleeping and plaque scores showed significant association with caries experience. Conclusion: ECC was more prevalent among 5-year-old children as compared to other age groups and moreover demographic factors such as mother's occupation, education, socioeconomic status, developmental characteristics such as enamel hypoplasia, feeding habits like prolonged and nocturnal bottle feeding and clinical parameters like plaque scores showed significant correlation with ECC.